Optimization of Recycle Use of Residual Ferrous Medium for Hydrogen Sulfide Bioremoval - Zheng, Yu; Zhang, Chaozheng; Wu, Xiaowei; Zhang, Jianguo; Sheng, Yu (Asian Journal of Chemistry, 2015)
One of the most potential approaches for hydrogen peroxide removal is reaction with ferric iron to produce elemental sulfur and ferrous iron followed with the oxidization of ferrous to ferric for recycling by the chemoautotrophy microorganism, Acidithiobacillus ferrooxidans. In the whole process there is no waste pollution produced. However, there are still a few large scale of this process because the recirculatory operation is not well established. In this work, the ferrous media after H2S removal was repeatedly used for Acidithiobacillus ferrooxidans cultivation by external nutrition (NH4OH, K2HPO4 and MgSO4·7H2O) supplement according to response surface methodology experiments. The recycle process was continuously operated for 40 days (six rounds) with a relatively stable oxidation rate of Fe2+ by supplementing the nutrient. In conclusion, it was a reliable method that the residual ferrous sulfate medium was recycled for Acidithiobacillus ferrooxidans cultivation with nutrition addition.